Unemployment and Income Inequality in Nigeria - Ewubare, Dennis B.; Kelechi C. Nnamdi, (IJRDO - Journal of Social Science and Humanities Research, 2020)
This study offers update on the assessments of unemployment and income inequality in Nigeria, using data from the General Household Surveys of the National Bureau of Statistics. Data were also obtained from World Bank and Central Bank of Nigeria. Based on an array of operational techniques, the study made the following major findings: first, the Nigeria economy is characterized by a persistent rise in national unemployment rate, with variability at some periods; which may persist. Second, the male labour force has a higher unemployment rate compared to their female counterpart. Third, unemployment is higher among youths, between 15-34years. Fourth, in addition to socioeconomic and demographic characteristics, post-secondary educational labour force is the dominant class of the unemployed. Fifth, a growing trend of income disparity was found between Nigerian states and regional clusters. Finally, it was revealed that rising unemployment accelerates income inequality. Besides, fiscal federalism, strategic economic policies aimed at providing sustainable employment encompassing the youths and graduates of post-secondary education should be put in place.